Proses PEMBENTUKAN KOSAKATA DAN FUNGSI BAHASA KELOMPOK GAY - Ahmad Wahyudin (LITERA, 2009)
This study aims to describe vocabulary formations and language functions in a gay community. The object was the language employed by such a community. The data were collected through listening, recording, and noting and were analyzed by means of the qualitative descriptive technique. The data trustworthiness was enhanced by careful observations and triangulation (data sources, relevant theories, and other observers). The findings are as follows. First, the vocabulary formations include (a) form addition, (b) form substitution, (c) utilization of short forms (abbreviations and acronyms), and (d) utilization of puns. Second, language in the gay community has four functions, i.e.: (a) emotive function, (b) referential function,(c) phatic function, and (d) conative function.